2021
DOI: 10.3390/f13010009
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Living Environments, Self-Rated Health Status and Perceptions of Urban Green Space Benefits

Abstract: Urban green space (UGS) could contribute to sustainable urban development. Studying residents’ perception of UGS ecological benefits could provide the empirical basis to improve UGS management and quality of life. Based on the questionnaire surveys of 432 residents in Beijing, assisted by non-parametric statistical tests, this paper assessed the relationships between residents’ living environments and self-rated health status and their impacts on residents’ perceptions of UGS ecological benefits. We paid atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…However, the local government has not yet specifically presented the area or target area for urban green space expansion. Secondly, investigating and understanding the needs of residents, especially the location and size of new green spaces and related facilities, can increase the effectiveness and sustainability of policies [ 95 , 96 , 97 ]. Understanding the impact of COVID-19 on the use of urban infrastructure can provide insights for space management and can be used to support the decisions about planning to manage and maintain urban green spaces in the future [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the local government has not yet specifically presented the area or target area for urban green space expansion. Secondly, investigating and understanding the needs of residents, especially the location and size of new green spaces and related facilities, can increase the effectiveness and sustainability of policies [ 95 , 96 , 97 ]. Understanding the impact of COVID-19 on the use of urban infrastructure can provide insights for space management and can be used to support the decisions about planning to manage and maintain urban green spaces in the future [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was suggested that residents on the urbanization gradient showed differentiated understanding on the green space benefits, such as the heat island effect mitigation and biodiversity enhancement [45]. More directly, a study in Tokyo suggested that bird or plant species with more obvious traits were perceived by more visitors, and a strengthened familiarity with local species which is less noticeable could enhance their perception of neighborhood biodiversity [6].…”
Section: Discussionmentioning
confidence: 99%
“…Most scholars study the direct impact of living environment factors on subjective well-being by analyzing surrounding facilities, community integration and neighborliness, housing conditions and housing quality, and using correlation analysis and regression analysis. There is many research on the impact of living environment on residents' subjective well-being, including sustainable and smart cities [1], community cohesion and social support [2], urban green space [3,4], ethnic composition within the community [5], different genders proportion [6], and age [7] etc. However, there are relatively few studies on special areas such as historic districts.…”
Section: Introductionmentioning
confidence: 99%